Peptide Nucleic Acids, Morpholinos and Related Antisense Biomolecules - Janson, Christopher G.; During, Matthew J.; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
This volume is unique to the existing literature in the Peptide Nucleic Acid field, in that it focuses on comparing and contrasting PNA with other available oligonucleotide homologues and considers areas in which these biomolecules could be profitably applied to clinical and diagnostic applications. Part I of the book addresses comparative strengths and weaknesses of various nucleoside homologues. Part II of the book addresses specific translational or clinical applications for PNA and related antisense biomolecules. The editors have succeeded in presenting a balanced yet broad view of the methods available for gene targeting and modification.
Research Applications -- The Many Faces of PNA -- Modulation of Nucleic Acid Information Processing by PNAs -- Targeted Gene Delivery -- Imaging Gene Expression in the Brain with Peptide Nucleic Acid (PNA) Antisense Radiopharmaceuticals and Drug Targeting Technology -- Receptor-Specific Targeting with Complementary Peptide Nucleic Acids Conjugated to Peptide Analogs and Radionuclides -- Morpholinos and PNAs Compared -- Chemistry of Locked Nucleic Acids (LNA) -- Recent Applications of RNA Interference (RNAi) in Mammalian Systems -- Clinical Applications -- Peptide Nucleic Acids as Epigenetic Inhibitors of HIV-1 -- Therapeutic Uses of Peptide Nucleic Acids (PNA) in Oncology -- PNAs as Novel Cancer Therapeutics -- Medicinal Chemistry of Plasmid DNA with Peptide Nucleic Acids -- Locked Nucleic Acids (LNA) and Medical Applications -- Peptide Nucleic Acids as Agents to Modify Target Gene Expression and Function -- Peptide Nucleic Acids -- The Use of PNAs and Their Derivatives in Mitochondrial Gene Therapy -- Gene Silencing through RNA Interference -- Transcriptional Activation of Human CREB Gene Promoter Using Bis-PNA (Peptide Nucleic Acid).
Keywords: Medicine; Human genetics; Immunology; Neurosciences; Biotechnology; Medical biochemistry; Biochemistry; Biomedicine; Human Genetics; Medical Biochemistry; Immunology; Neurosciences; Biotechnology; Biochemistry, general; Electronic books